2012
DOI: 10.1002/ajhb.22237
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term trends in food availability, food prices, and obesity in samoa

Abstract: Objectives To describe long term food availability and prices from 1961 to 2007 and BMI trends from 1980–2010 in Samoa, and to contextualize these trends within political, economic, cultural, behavioral, and climatic influences. Methods National level data on food availability and pricing were obtained from the open access database FAO (http://faostat.fao.org). Data for Samoa were collected from annual food balance sheets available for the period 1961 to 2007. Mean BMI for Samoan men and women ages 35–44 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 31 publications
3
65
0
Order By: Relevance
“…Imported foods range from corned beef, turkey tails and meat flaps to rice, sugar, instant noodles, Food security in the island Pacific biscuits and soft drinks (e.g. Evans et al 2001;Dixon and Jamieson 2005;Cassels 2006;Oles 2007b;Foster 2008;Gewertz and Errington 2010;Errington et al 2013;Rudiak-Gould 2009;Thow et al 2010;Seiden et al 2012). Rice and flour have become food staples even in quite remote communities, sometimes eaten without accompaniments.…”
Section: Nutrition and Healthmentioning
confidence: 97%
“…Imported foods range from corned beef, turkey tails and meat flaps to rice, sugar, instant noodles, Food security in the island Pacific biscuits and soft drinks (e.g. Evans et al 2001;Dixon and Jamieson 2005;Cassels 2006;Oles 2007b;Foster 2008;Gewertz and Errington 2010;Errington et al 2013;Rudiak-Gould 2009;Thow et al 2010;Seiden et al 2012). Rice and flour have become food staples even in quite remote communities, sometimes eaten without accompaniments.…”
Section: Nutrition and Healthmentioning
confidence: 97%
“…The relatively high potassium intake levels align with the findings of lower-than-anticipated sodium intake, suggesting that the transition to processed food consumption 35 in Samoa is limited, with the diet still including substantial intakes of fresh vegetables. 36 Preliminary analysis of the Food and Agriculture's Household Income and Expenditure Survey confirms that around 55% of total energy intake is derived from vegetables (primarily root vegetables). This is in contrast to Fiji where salt intake is much higher, partly because of the influence of the Indian diet but likely also because of the greater transition toward high-salt processed foods.…”
Section: Study Limitations and Strengthsmentioning
confidence: 99%
“…Rates of obesity have been increasing dramatically in the last decades as the population experienced rapid modernization (39). As a consequence of this rapid modernization, Samoans have undergone a nutrition transition, largely abandoning their neo-traditional diets and acquiring a modern dietary pattern and sedentary lifestyle (39, 40). In a study conducted in 2002–03 among 723 American Samoans and 785 Samoans, we have shown previously that a modern dietary pattern was significantly associated with metabolic syndrome in Samoa and with increased triglyceride levels in both polities (41).…”
Section: Introductionmentioning
confidence: 99%